النقد الرجالي عند الشيخ محمد حسن المظفر قدس سره ت. 1375 هـ : رجال الصحاح الستة أنموذجاً - المظفر، علي عبدالحسين Almuzaffar, Ali Abdulhussien (المنتدي الوطني لأبحاث الفكر والثقافة, 2015)
The critical studies men in the modern science of specialized branch of the men knew which means knowing the conditions of the narrators Studies injured, modify, and these studies embarked novel scientists to comply with rules and put their curriculum since the beginning of recorded talk and annexed in encyclopedias and works of different Haddithih did these studies are limited to a class without the other, but overlapped among the various intellectual trend for Muslim Scholars through men Sindh overlap they have held this research to the study of contemporary scientific figure in Najaf scientific same direction School Fiqh front through his research and explore the depths of men's studies modern men support and wrote the general people, or what is known as (Asahah the six) This research along with the men's criticism has been picking up at Sheikh Muzaffar through the introduction of his book (honesty) signs, and represented the status methodological rules for his study of the approach authorship in Alhdithip six books by Sheikh Muzaffar focus on the router for these books criticism by scholars and prevented internal turmoil in the evaluated on the other hand, while engaged Sheikh Muzaffar in the other side of the second typing (disclosure ...) to Applied study evaluated men basis for the modern novel books Asahah statement if every one of the private, has characterized the study Sheikh Muzaffar methodology monetary rigor scientific method neutral during his return to reliable sources have in the criticism of the men confirmed it to information and impartial attitude survey accuracy, that Sheikh Muzaffar that was not just a conveyor to the opinion of the other, but it was his opinion discretionary Barzah after considering the views of those who transported them and this is what ensures Find Baldrasth and highlighted. The Sheikh Mohammed bin Hassan Sheikh Mohammad Muzaffar (1301 E - 1883/1375 E - 1957) (a) of the scholars of Najaf Ashraf School and eminent scientists of his era was characterized by scientific Bmosusah in Tassanifa Valve in Fiqh inferential (rules -oho wrote jurisprudential constructive to explain the laws of Islam), written in the speech and protest his encyclopedia (honesty) signs, and in his book men (disclosure of narrators Asahah) has in literature and poetry sold large.
Keywords: المظفر، محمد حسن، ت. 1375 هـ -- الجرح و التعديل -- علم الرجال -- كتب الصحاح -- الأحاديث النبوية